Physiotherapy of Charcot–Marie–Tooth disease - N. A. Shnayder; S. I. Goncharova (Нервно-мышечные болезни, 2015)
In the article there is a review the latest achievements in the field of physiotherapy Charcot–Marie–Tooth disease (CMT). Describes some of the techniques non-pharmacological treatment, the goal of physiotherapy application depending on the pathogenesis, clinical manifestations of the disease, electromiographic tests. Here there are recommendations for sanato¬rium treatment. On the basis of personal observations in the article presents the author's patterns of treatment for CMT patients.